Arabic Language Learning Approach Using Smart Technology in Higher Education - Zainul Arifin; Ayu Desrani; Apri Wardana Ritonga; Faisal Mahmoud Adam Ibrahim (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2023)
This research aimed to analyze the implementation framework of smart technology in learning Arabic at the Nusantara Islamic University of Bandung. Researchers adopted a mix-method, namely quantitative and qualitative. Quantitative data was obtained from distributing questionnaires from the application of the smart technology used, and qualitative data were obtained from interviews with students studying the Arabic language and literature at the Nusantara Islamic University of Bandung. Quantitative data were analyzed descriptively, namely calculating the percentage of technology use. The results of this study indicate that the use of technology uses smart technology as a teaching and learning tool. The use of smart technology makes learning easier, more interactive, and more effective. Other technologies are used such as social media, and language laboratories with different hardware and software facilities that support learning Arabic. The use of smart technology is overshadowed by positive and negative impacts that must be the main concern of all users.